2021
DOI: 10.1177/15459683211011220
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Integrity Relates to Improvement of Upper-Extremity Function Following Intensive Rehabilitation in Children With Unilateral Spastic Cerebral Palsy

Abstract: Background The corpus callosum (CC) plays an important role in upper extremity (UE) function. The impact on UE function in children with unilateral spastic cerebral palsy (USCP) and improvements following intensive interventions remain unknown. Objectives To examine the (1) relationship between UE function and CC integrity and (2) relationship between CC integrity and changes in UE function following intensive interventions. Methods We retrospectively analyzed clinical and neuroimaging data from a sample of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This is further supported by studies on other pediatric populations which have shown that damage to certain neurological networks is associated with motor planning deficits in children with tumors [ 133 , 134 ] or in children with neurodevelopmental disorders [ 135 , 136 ]. In addition, the results in bilateral tasks cannot be compared to those of unilateral tasks as both types of tasks rely on different neural networks [ 137 , 138 ]. This review also included a large age range to explore the atypical maturation of motor processes from a developmental perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by studies on other pediatric populations which have shown that damage to certain neurological networks is associated with motor planning deficits in children with tumors [ 133 , 134 ] or in children with neurodevelopmental disorders [ 135 , 136 ]. In addition, the results in bilateral tasks cannot be compared to those of unilateral tasks as both types of tasks rely on different neural networks [ 137 , 138 ]. This review also included a large age range to explore the atypical maturation of motor processes from a developmental perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Greater damage to the motor area of the CC is associated with worse manual dexterity in the more and less affected hands [101]. Further, worse manual dexterity moderately relates to the reduced structural integrity of the CC [24]. Therefore, although the motor and sensory tracts show relationships with grasp impairments in children with USCP, the impairments may not be a sensory tract or motor tract problem.…”
Section: Relationship Between Sensory and Motor Information And The C...mentioning
confidence: 99%
“…The CC is thought to transfer somatosensory information between hemispheres [22,23]. However, children with USCP display structural abnormalities of the CC [24,25]. Thus, when the sensory and motor tracts are in different hemispheres and somatosensory information needs to be transferred between hemispheres, damage to the CC may further contribute to grasp impairments in children with this sensory-motor dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…The CC is considered important for the efficient sensorimotor function of the whole body. The structural properties of CC have been repeatedly associated with the bimanual performance both in CP (Weinstein et al 2014 ; Hung et al 2019 ; Robert et al 2021 ) and in normal development (for a review, see Gooijers and Swinnen 2014 ). In addition, the severity of CP has been linked with the degree of the structural CC deficits: greater motor impairments according to the Gross Motor Functioning Classification Scale (GMFCS), have been associated with a smaller CC volume (Kułak et al 2007 ; Reid et al 2015 ) and decreased fractional anisotropy (FA) values in the CC (Lee et al 2011 ; Ballester-Plané et al 2017 ; Jiang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%